Students' Anxiety and Motivation to Speak English at Islamic Boarding School - Sayuri, Sayuri; Malihah, Noor; Fauzan, Umar (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Background: This study was conducted to find out the correlations and influences of students’ anxiety and motivation to students’ speaking English achievement. Methodology: One hundred and thirteen students Islamic Boarding School of Nabil Husein Samarinda participated in this study. A stratified random sampling technique was used in this study. Foreign Language Classroom Anxiety (FLCAS) and Attitude Motivation Test Battery (AMTB) were used as instruments. Multiple Regression and Path Analysis were used as data analysis techniques to analyze the data. Findings: 80.4% of students’ anxiety influenced to students’ speaking English Achievement. The next finding showed that students’ anxiety correlated to students’ motivation at 94.7%. It indicated a strong correlation where the degree of correlation at 0.897. As well the students’ motivation also affected students’ speaking English achievement on the degree at 79.9%. The last finding showed that students’ speaking English was affected by students’ anxiety and motivation simultaneously. Conclusion: This article explains how the students’ anxiety and motivation influence speaking English achievement. Originality: This research was conducted to find out the correlations and the influences of students’ anxiety, and students’ motivation to students’ speaking English achievement.